New and little-known sun-moth species from Australia (Lepidoptera, Castniidae) - Kallies, Axel; Edwards, Edward D.; Williams, Andrew A. E. (Zootaxa, 2020)
In this study, we designate lectotypes and fix the identities of two Australian Castniidae species, Synemon sophia (White, 1841), the type species of Synemon Doubleday, 1846, and Synemon parthenoides R. Felder, 1874. Furthermore, we describe seven new species of Castniidae from Western Australia, two new species of the Synemon sophia group, Synemon anthracica Kallies & Edwards sp. n. and Synemon crocea Kallies & Edwards sp. n., three species in the Synemon magnifica Strand, 1911 group, Synemon semaphora Kallies & Edwards sp. n., Synemon angustiptera Kallies & Edwards sp. n. and Synemon petrophila Kallies & Edwards sp. n., one new species of unclear affinity, Synemon cacumina Kallies & Edwards sp. n., and one new species related to Synemon directa Westwood, 1877, Synemon victoriae Kallies & Edwards sp. n. We report Restionaceae, a host-plant family not previously recorded for Castniidae.